Low internal exposure and absence of adverse effects in workers exposed to high air levels of inorganic selenium. (1st December 2018) - Greiner, Annette; Göen, Thomas; Hildebrand, Jörg; Feltes, Ruth; Drexler, Hans
Graphical abstract: Highlights: Occupational exposure to high air concentrations of Se and inorganic Se compounds. Only moderate increase of the internal Se status in the exposed individuals. Indication of an extremely low inhalative resorption of Se and inorganic Se compounds. No indication of adverse health effects in occupational Se-exposed individuals. Abstract: Selenium is an essential trace element for humans, but adverse health effects may occur after elevated intake. The margin between it is small. This study aimed to assess external and internal exposure in workers of a selenium-processing plant, in which elemental and inorganic selenium occurred. Selenium was analyzed in the form of the selenium concentration in plasma (Se-P), in erythrocytes (Se-RBC) and in personal air samples (Setotal -Air) of 17 exposed workers. Internal exposure was compared to 20 controls without occupational selenium exposure. For potential effects, glucose, HbA1c, proinsulin, prothrombin time and GPX were determined. Setotal -Air had a maximum of 2394 μg/m 3 (median 319 μg/m 3 ), containing a small water-soluble fraction (median 12.7 μg/m 3, range 0.07–975 μg/m 3 ). Se-P of the exposed ranged from 62 to 123 μg/L (median 105 μg/L), whereas the median of Se-RBC was 63.4 μg/L blood (range 51.9–92.7 μg/L). Both were significantly higher than the controls. No significant difference was found for the effect parameters. Biological effect monitoring of employees occupationally exposed to very high levels of selenium and inorganic selenium compounds did not show any indication of adverse health effects. The moderate increase of the internal selenium exposure compared to the high ambient exposure to selenium and its compounds suggests an efficient air protection or an extremely low resorption of elemental and inorganic species of selenium via inhalation.